出血性上部消化管潰瘍に対するNBCA塞栓術 - 嶺 貴彦; 村田 智; 小野澤 志郎; 上田 達夫; 山口 英宣; 杉原 史恵; 安井 大祐; 宮内 雅人; 田島 廣之; 汲田 伸一郎 (Nihon Fukubu Kyukyu Igakkai Zasshi (Journal of Abdominal Emergency Medicine), 2014)
The efficacy and safety of transcatheter arterial embolization with n-butyl cyanoacrylate (NBCA-TAE) for Forrest I gastroduodenal ulcer bleeding were evaluated from the experience of 26 patients who underwent NBCA-TAE. Shock indices prior to and immediately after NBCA-TAE were compared to determine changes in hemodynamics. Days to Forrest type Ⅲ, as assessed by follow-up endoscopy, was used as an indicator of the healing process. Immediate hemostasis was achieved in all the patients, and the shock index significantly (p<0.001) improved from before (1.09±0.088) to immediately after NBCA-TAE (0.68±0.031). Sequential mucosal healing processes were observed in all the patients, and the number of days to Forrest type Ⅲ was 9.0±3.8. NBCA-TAE is an effective and safe method for the control of gastroduodenal ulcer bleeding, in terms of contribution to hemodynamics and healing process of the gastroduodenal mucosa. However, understanding the behavior of NBCA within the circulation and adequate administration techniques are necessary. 内視鏡的止血困難例26例を対象に，出血性上部消化管潰瘍に対するN-butyl-2-cyanoacrylate（NBCA）を用いた動脈塞栓術後の循環動態変化と粘膜治癒過程に関する評価・検討を行った。塞栓術により全例で即時的な止血と有意な循環動態の改善が確認された。塞栓術前の潰瘍病変は全例Forrest Ⅰ（Ia 20，Ib 6）であり，塞栓術後には明らかな虚血性粘膜障害は認められず，11±7.9日で Forrest Ⅲまでの改善が確認された。NBCAは適正な使用下では潰瘍治癒過程において大きな妨げにはならないものと考えられ，安全かつ有用性の高い塞栓物質であると考えられた。